Atrial fibrillation - management, the challenge and new solutions 2 - Olshansky, Brian (Henry Stewart Talks, 2015)
Approach to treatment, Rate control in AF, Is sinus rhythm needed?, ACC/AHA guidelines – Rhythm control: data from clinical trials, Pulmonary veins can trigger AF, AF ablation, Ablation vs. drugs